2021
DOI: 10.20473/jbk.v10i2.2021.191-201
|View full text |Cite
|
Sign up to set email alerts
|

Options of Long-Term Contraceptive Methods in Married Women in South Sulawesi (Analysis of Idhs 2017)

Abstract: The long-term contraceptive method is an effective method for preventing pregnancies. However, users of long-term contraceptive methods are considerably lower compared to those of non-long-term contraceptive methods in South Sulawesi. The research objective was to examine the determinants of choosing long-term contraceptive methods in South Sulawesi. This study used data from the 2017 Indonesia Demographic and Health Survey by analyzing 583 married women who were using contraception in South Sulawesi. A descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
0
1
Order By: Relevance
“…Firstly, the age of women (X1) does not significantly impact their decision, which contrasts with research by Darsono et al (2020) and Gayatri (2022), who found that age, particularly among women over 35, significantly influences the choice of LARC. Similarly, the education level of women (X2) shows no significant effect on this choice, diverging from findings by Al-Husban et al (2022) and Azis et al (2021).…”
Section: Determinants Of Choosing Larc and Non-larc Among Family Plan...contrasting
confidence: 62%
“…Firstly, the age of women (X1) does not significantly impact their decision, which contrasts with research by Darsono et al (2020) and Gayatri (2022), who found that age, particularly among women over 35, significantly influences the choice of LARC. Similarly, the education level of women (X2) shows no significant effect on this choice, diverging from findings by Al-Husban et al (2022) and Azis et al (2021).…”
Section: Determinants Of Choosing Larc and Non-larc Among Family Plan...contrasting
confidence: 62%
“…Individuals who own amount child more of than 2 is at risk tall to health Good for the Mother or child , p This can reduced as well as prevented with a family planning program using MKJP. Research conducted in South Sulawesi found that the more Lots amount child, the higher the more tendency is high For use contraception period long namely 3 times more Lots compared to women who have <2 children (Aziz et al, 2021). Other research conducted in Ethiopia was also found that women who give birth to 3-4 children used MKJP 2 more times Possible compared to with those who give birth to 1-2 children (Desalegn et all, 2019).…”
Section: Analysis Bivariate Connection Amount Child With Behavior Use...mentioning
confidence: 95%
“…The safety of the method, efficacy, return of fertility are not the only considerations influencing contraceptive choice, but ease of use, convenience, the impact on sexual relationships, as well as spousal support and religious beliefs also play a role in contraceptive selection. [15] A research on contraceptive use conducted by Agustini in Puger Jember in 2015 found that contraceptive use is related to age, the number of living children, maternal education, the location of family planning services, and the cost of contraception, but it is not related to the desired number of children or family income [7]., [16].…”
Section: Introductionmentioning
confidence: 99%